2011
DOI: 10.1074/jbc.m110.209353
|View full text |Cite
|
Sign up to set email alerts
|

Conserved Noncanonical Residue Gly-126 Confers Instability to the Middle Part of the Tropomyosin Molecule

Abstract: Tropomyosin (Tm) is a two-stranded ␣-helical coiled-coil protein with a well established role in regulation of actin cytoskeleton and muscle contraction. It is believed that many Tm functions are enabled by its flexibility whose nature has not been completely understood. We hypothesized that the well conserved non-canonical residue Gly-126 causes local destabilization of Tm. To test this, we substituted Gly-126 in skeletal muscle ␣-Tm either with an Ala residue, which should stabilize the Tm ␣-helix, or with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
63
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(74 citation statements)
references
References 40 publications
10
63
0
Order By: Relevance
“…It was previously reported that flexibility of the middle region of TM, where residue 137 lies, is not crucial for actin binding and that D137L substitution does not alter the actin binding properties of TM (11,12). However, a direct interaction between the C-terminal mobile domain of cTnI and residue 146 of TM was previously proposed by Mudalige et al (56).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…It was previously reported that flexibility of the middle region of TM, where residue 137 lies, is not crucial for actin binding and that D137L substitution does not alter the actin binding properties of TM (11,12). However, a direct interaction between the C-terminal mobile domain of cTnI and residue 146 of TM was previously proposed by Mudalige et al (56).…”
Section: Discussionmentioning
confidence: 92%
“…As determined with DSC, the ␣-TM-D137L variant has higher thermostability than WT, suggesting decreased flexibility. In the description of the ␣-TM and ␣-TM-D137L variant, we have used the term "flexibility" as has been common in previous papers (8,9,11,12). However, it should be recognized that in our case describing a protein as flexible is an interpretation of determinations of stability that may have different interpretations.…”
Section: ␣-Tropomyosin (␣-Tm)mentioning
confidence: 99%
“…Among Tm noncanonical amino acids, recent studies have examined two highly conserved residues in the middle part of the aaTm molecule: D137 (a charged residue in a d hydrophobic position) and G126 (a small, neutral residue in a g charged position). Replacement of these residues with canonical ones, D137L and G126R (9,10), was shown in solution studies to significantly increase coiled-coil stability and decrease molecular mobility or flexibility (9,(11)(12)(13). A significant decrease in the flexibility of reconstructed thin filaments with the combined D137L/G126R substitution was also shown by means of the two-bead optical trap technique (14).…”
Section: Introductionmentioning
confidence: 94%
“…Interestingly, Ca 2þ regulation dynamics in the intact thin filament are also affected, as shown by measurements of thin-filament-induced activation of S1 ATPase activity in the presence of D137L or G126R aaTm (9,10), and by the maximal sliding velocity of regulated actin filaments in in vitro motility assays (15,16). All of these studies reported a clear functional change in the presence of one or both stabilizing substitutions and a generalized increase in apparent Ca 2þ sensitivity.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation